Innovative Perspectives of Biogenic Synthesis of Metal Nano Composites and Its Biological Studies- An Overview - Kavitha, Ganesan; Abirami, Natarajan (Recent Progress in Science and Technology Vol. 6, 2023)
Nanotechnology is an emerging branch of pharmaceutical science in which particles expand at nano-size and become highly responsive as they vary with their unique counterparts. Nanoparticles (NPs) are used in biological use because of their unique physical and chemical properties. NPs exhibits advanced properties such as strength, surface area, high reactivity, stability, and sensitivity owing to their small size. NPs are integrated by numerous methods for research and commercial applications and can be divided into three categories: chemical, mechanical, and physical processes. This article provides an overview of nanoparticles, including their types, properties, synthesis processes, and environmental uses. In medical science, metal and metal oxide-supporting nanoparticles have demonstrated a considerable therapeutic effect. Mechanisms involving nanoparticle interactions with plant cells and animals can be employed to determine their significance and improve their function in health and medicinal applications. Antibiotic resistance and antibacterial activity of metal-backed nanoparticles are discussed in various ways. Despite advancements, intense research on their effectiveness in addressing modern challenges is required. In this regard, the current work investigates the role of several types of metal-supporting nanomaterials in many fields, including antibacterial and anticancer. Metal-supported nanomaterials are expected to play a prominent role both in medical and electrochemical fields including sensing and energy applications.